1972
DOI: 10.1111/j.1432-1033.1972.tb02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Phosphates and Stability of Phosphate Triesters in DNA

Abstract: A method is presented to measure the alkylation of phosphates in DNA after a treatment with an alkylating agent. Using this method, we have shown that phosphate alkylation represents 15O/, of total alkylation when DNA is alkylated with ethyl methanesulfonate and only l o / , of total alkylation when DNA is alkylated with methyl methanesulfonate. Experiments are also presented which show that phosphate triesters resulting from the alkylation of DNA by ethyl methanesulfonate are very stable, most of them remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
1
2

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 20 publications
6
67
1
2
Order By: Relevance
“…Alkylated guanines are known to undergo both cleavage [33] and depurination, even at neutral pH ; this rate increases at lower pH [34,35]. Phosphotriester formation has also been suggested to account for up to 20 % of DNA methylation but is considered to be relatively stable to hydrolysis [36,39]. To test for loss of label, chromatin labeled with the reagent was incubated for several hours under our standard conditions of reaction (Table 2).…”
Section: Depurinationmentioning
confidence: 99%
“…Alkylated guanines are known to undergo both cleavage [33] and depurination, even at neutral pH ; this rate increases at lower pH [34,35]. Phosphotriester formation has also been suggested to account for up to 20 % of DNA methylation but is considered to be relatively stable to hydrolysis [36,39]. To test for loss of label, chromatin labeled with the reagent was incubated for several hours under our standard conditions of reaction (Table 2).…”
Section: Depurinationmentioning
confidence: 99%
“…Esterification of the phosphate residues in DNA by these alkylating agents produces triesters which are stable under conditions ofmild hydrolysis (Bannon & Verly, 1972;Lawley et al, 1973), but in RNA these products are unstable (Brown & Todd, 1955). Their presence in poly(A) after incubation with ethyl methanesulphonate was indicated by chain breakage, but this was not observed in similar experiments with methyl methanesulphonate (Ludlum, 1969).…”
mentioning
confidence: 97%
“…Although it is over 20 years since it was first proposed that phosphotriesters might be present in DNA after reaction with alkylating agents (Elmore et al, 1948), uncertainty surrounded this issue until direct evidence was provided for the existence of alkyl phosphates in DNA, by Bannon &Verly (1972). They found that after treatment with methyl methanesulphonate or ethyl methanesulphonate in vitro alkylation of the phosphate residues accounted for 1 and 15% of the total reaction respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphotriesters have long been known to occur in both DNA and RNA as a result of exposure to certain toxins and chemicals (e.g., see Bannon and Verly 1972;Singer et al 1975). Formation of a phosphotriester similar to the type proposed to exist in RNA X was observed to occur as a side reaction during chemical synthesis of DNA (Weimann and Khorana 1962).…”
Section: Phosphotriesters Frequently Occur In Nucleic Acidsmentioning
confidence: 99%